PERAN PEJABAT PEMBUAT AKTA TANAH (PPAT) DALAM PELAKSANAAN PENDAFTARAN TANAH DI KABUPATEN GOWA - Muhammad Irsan Sugeng (Jurnal Yustisiabel, 2020)
Land is very important in people's lives and development, so it needs to get legal protection. This writing aims to know the role of the Land Deed Making Officer (PPAT) in the implementation of Land Registration as well as the hindering factors that affect it in Gowa Regency. The type of research used in this writing is empirical juridical. The role of the Land Deed Making Officer (PPAT) in the implementation of land registration in Gowa Regency is to create an authentic deed that plays a role in providing juridical data on the change of land registration data. In carrying out its duties, Gowa Regency PPAT sticks to the prevailing laws and regulations including its implementation rules. The factors that hinder the role of the Land Deed Administration (PPAT) in the implementation of Land Registration in Gowa Regency are the inability of the parties in completing the requirements related to taxation, Do not own or have proof of ownership, and the land rights holder has died.